2013
DOI: 10.1007/s00249-013-0931-z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of adhesion molecule domains on neutrophil membranes: surfing the dynamic cell topography

Abstract: Lateral organization and mobility of adhesion molecules play a significant role in determining the avidity with which cells can bind to target cells or surfaces. Recently, we have shown that the lateral mobility of the principal adhesion molecules on neutrophils is lower for rolling associated adhesion molecules (RAAMs: L-selectin and PSGL-1) than for β2 integrins (LFA-1 and Mac-1). Here we report that all four adhesion molecules exhibit distinct punctate distributions that are mobile on the cell surface. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Immunofluorescence staining revealed that MMP-9 exhibited punctate distribution similar to that reported for CD11b (45), but did not colocalize with CD11b, which is typically expressed on membrane ruffles (46). It remains to be determined whether MMP-9 expressed at the PMN surface associates with another protein or nonspecifically coats PMN membranes.…”
Section: Discussionmentioning
confidence: 68%
“…Immunofluorescence staining revealed that MMP-9 exhibited punctate distribution similar to that reported for CD11b (45), but did not colocalize with CD11b, which is typically expressed on membrane ruffles (46). It remains to be determined whether MMP-9 expressed at the PMN surface associates with another protein or nonspecifically coats PMN membranes.…”
Section: Discussionmentioning
confidence: 68%
“…Sundd and colleagues have recently made some interesting observations on how these neutrophils maintain contact with EC during rolling [ 32 ]. During the initial contacts with EC through selectins/selectin ligands, the structure of the neutrophil cell membrane is modified by reorganization of both cytoskeleton and surface adhesion molecules leading to the formation of an extended protrusion called sling [ 33 ]. This structure is formed from a membrane tether at the back of the rolling neutrophil like an anchor before it is wrapped around the rolling leukocyte and swings to the front of the cell to recontact the EC.…”
Section: Mechanisms Exploited By Neutrophils To Achieve Extravasatmentioning
confidence: 99%
“…Comparison of diffusion of several proteins can show the selectivity of proteins for certain domains [16,17], while the increase in diffusion coefficient (D) upon cholesterol depletion indicates affinity of the concerned proteins for cholesterol enriched domains [16]. Diffusion of whole domains containing different adhesion molecules was measured by temporal ICS (TICS) and found to correlate with the function of the respective molecules [18]. The selectivity of proteins for certain domains was also demonstrated by Lillemeier et al [19].…”
Section: Membrane Organizationmentioning
confidence: 85%
“…1). Diffusion of whole domains containing different adhesion molecules was measured by temporal ICS (TICS) and found to correlate with the function of the respective molecules [18]. Diffusion of whole domains containing different adhesion molecules was measured by temporal ICS (TICS) and found to correlate with the function of the respective molecules [18].…”
Section: Membrane Organizationmentioning
confidence: 99%
See 1 more Smart Citation